Pembuatan Video Company Profile Sebagai Penunjang Informasi dan Promosi Pada PT. Daiichi Elevator Indonesia - Rifai, Danang; Astriyani, Erna; Indria, Upi (Technomedia Journal, 2018)
The development of information technology is so rapid to utilize this development as a means of socialization of good promotional information programs for products that are intended to be introduced to the public, for this reason a media is needed that can be useful as a public attraction. As with PT. Daiichi Elevator Indonesia which until now promotion program information support facilities are considered not to provide an effective communication function for that matter as the need for information support and future promotion programs requires forms of media design that can answer the needs of information facilities that are effective, efficient, and on target . Information becomes important because with information someone will know new things that are not yet known. Information is shared through print media or electronic media, from which the public can find information. In this PT. Daiichi Elevator Indonesia does not have a media in the form of a company profile video to support information and promotion. The research method used in this research is problem analysis method, data collection method, data analysis, and design analysis method. In this concept there are stages of preproduction, stages of production, and stages of postproduction. From the results of the media profile video design can increase sales and information to people who want to know more clearly about the elevator / escalator at PT. Daiichi Elevator Indonesia to get to know more about the profile details owned by PT. Daiichi Elevator Indonesia. Keywords: Video Profile, Information, and Promotion